Family relationships and troubled masculinities: the experience of young men in contact with social care services - Michael Ward (Different Childhoods: non/normative development and transgressive trajectories [edited by O'Dell, L., Brownlow, C., and Bertilsdotter Rosqvist, H.], 2018)
Robb, M., Featherstone, B., Ruxton, S. and Ward, M.R.M. (2017) Family relationships and troubled masculinities: the experience of young men in contact with social care services, in O'Dell, L., Brownlow, C., and Bertilsdotter Rosqvist, H., (Eds) Different Childhoods: non/normative development and transgressive trajectories, London, Routledge. 72-84.